Flash-evaporated small molecule films toward low-cost and flexible organic light-emitting diodes. Issue 41 (2nd October 2017) - Wang, Bo; Wang, Zhao-Kui; Liang, Jian; Li, Meng; Hu, Yun; Liao, Liang-Sheng
Abstract : A flash evaporation method was developed to fabricate small molecule-based multilayer organic light-emitting diodes (OLEDs). The new method can reduce the fabrication cost and avoid the issue of intersolubility in solution-processed multilayer OLEDs. Abstract : The high cost of vacuum thermal evaporation and the challenging fabrication of multilayer devices by the solution processing method restrict the commercialization of organic light-emitting diodes (OLEDs). Herein, we introduce a flash evaporation method where an organic film pre-coated on a silicon wafer is re-deposited by sudden exposure to high temperature (∼1000 °C) in a rough vacuum to fabricate small molecule-based multilayer OLEDs. The flash-evaporated organic films maintain the original molecular structure after flash evaporation. Compared with the random molecular orientation of spin-coated small molecule films, flash-evaporated films have a high degree of molecular orientation perpendicular to the substrate surface. As a result, flash-evaporated OLEDs exhibit improved efficiency with low roll-off compared with spin-coated devices. The successful fabrication of a flexible, large-area (20 × 20 mm 2 ) OLED suggests the great potential of the flash evaporation method for fabricating flexible and large area OLEDs with low cost in the future.